Back Cover: Therapeutic antibodies under development for SARS‐CoV‐2 (View 2/2022). Issue 2 (21st March 2022) - Ma, Zetong; Zhu, MengMei; Zhang, Shuyi; Qian, Kewen; Wang, Chuqi; Fu, Wenyan; Lei, Changhai; Hu, Shi
Abstract : Research on antibody therapy for SARS‐COV‐2 is in the ascendant, including single antibody therapy and multiple antibody combinations. The multi‐drug combination is also called an antibody cocktail, which relies on different antibodies to target different epitopes so it can avoid immune escape caused by mutations in a better way and achieve a better curative effect. In article number 20200178, Shi Hu and co‐workers have portrayed antibody cocktails as a kind of cocktails which is a mixture of different liqueurs in different colors. As the last drop of liquid is added, a cocktail specially tuned to hit the virus will be finished.